Fin damage and growth parameters relative to stocking density and feeding method in intensively cultured European perch (Perca fluviatilis L.). Issue 2 (26th November 2019) - Stejskal, Vlastimil; Matoušek, Jan; Prokešová, Markéta; Podhorec, Peter; Křišťan, Jiří; Policar, Tomáš; Gebauer, Tatyana
Abstract: We evaluated the relationship of stocking density to survival, growth performance and fin condition of European perch Perca fluviatilis with hand feeding and self‐feeders. Hand‐fed perch (body weight 19.1 ± 5.1 g and total length 107 ± 9 mm) were reared at 0.5, 1.0, 1.5 and 2.0 fish/L. Self‐feeding perch (body weight 25.4 ± 3.9 g and total length 128 ± 7 mm) were reared at stocking densities of 0.6, 1.0 and 1.4 fish/L. Pond‐reared perch served as a comparison group for fin damage assessment. We found no differences in survival rate among stocking densities with either feeding method. Hand‐fed fish displayed the highest weight gain and SGR at stocking density of 0.5 fish/L. The self‐feeding fish showed a non‐linear association of weight gain with stocking density with the highest growth at 1.0 fish/L. Fin length was noticeably greater in pond‐reared fish compared with RAS‐reared fish regardless of feeding method. In both experiments, fin length relative to standard length showed a negative relationship with stocking density, with pectoral fins showing the greatest effect. Fin condition deteriorated with increasing stocking density, and growth was highest at 0.5 and 1.0 fish/L in hand‐fed and self‐feeding fish, respectively.